Cognitive Development of Elementary School Children Based on Parenting Patterns - Adita yanto; Pritasari Cintya (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to observe how the way parents educate their children affects the development of children's minds at the elementary school level, specifically in the ability to think critically, solve problems, and create. The research used a descriptive qualitative approach, with information drawn from relevant literature sources, and presented the data as it is without alteration. The findings of this study show that the parenting style applied by parents is very important in shaping children's cognitive abilities, including critical thinking, problem solving and logic skills. Parental involvement, positive communication, a favorable learning environment, and education provided by parents are instrumental in children's cognitive development. Parenting models have a major influence on children's cognitive development, and demonstrate the importance of choosing parenting methods that support children's independence, responsibility and critical thinking skills so that they can reach their full potential. To conclude, good parenting approaches and positive family interactions have a significant impact on children's cognitive development, which has a direct impact on their ability to learn.